Frequency and pattern of central lymph node metastasis in papillary carcinoma of the thyroid isthmus. (29th June 2015) - Song, Chang Myeon; Lee, Dong Won; Ji, Yong Bae; Jeong, Jin Hyeok; Park, Jung Hwan; Tae, Kyung
Abstract: Background: The purpose of this study was to evaluate the frequency and pattern of central lymph node metastasis in isthmic papillary thyroid carcinoma (PTC). Methods: We compared the clinical and pathological data of 45 patients with a single isthmic PTC and 149 patients with a single PTC located in the unilateral thyroid lobe, all of whom underwent total thyroidectomy and bilateral central neck dissection. Results: The rates of clinical, pathologic, and occult central lymph node metastasis were higher in the isthmus group than the non‐isthmus group. Central lymph node metastasis in the pretracheal and bilateral paratracheal lymph nodes was more frequent in the isthmic PTC group than in the non‐isthmus group. On multivariate analysis, isthmic location of the tumor was an independent risk factor for central lymph node metastasis. Conclusion: Complete bilateral central neck dissection should be considered for isthmic PTC because of the high rate of bilateral central lymph node metastasis, especially to pretracheal and bilateral paratracheal lymph nodes. © 2015 Wiley Periodicals, Inc. Head Neck 38: E412–E416, 2016